Racial differences in survival and response to therapy in patients with metastatic colorectal cancer: A secondary analysis of CALGB/SWOG 80405 (Alliance A151931). Issue 20 (10th August 2021) - Snyder, Rebecca A.; He, Jun; Le‐Rademacher, Jennifer; Ou, Fang‐Shu; Dodge, Andrew B.; Zemla, Tyler J.; Paskett, Electra D.; Chang, George J.; Innocenti, Federico; Blanke, Charles; Lenz, Heinz‐Josef; Polite, Blasé N.; et al.
Abstract : Background: The objective of this study was to evaluate the association between self‐identified race and overall survival (OS), progression‐free survival (PFS), and response to therapy among patients enrolled in the randomized Cancer and Leukemia Group B (CALGB)/SWOG 80405 trial. Methods: Patients with advanced or metastatic colorectal cancer who were enrolled in the CALGB/SWOG 80405 trial were identified by race. On the basis of covariates (treatment arm, KRAS status, sex, age, and body mass index), each Black patient was exact matched with a White patient. The association between race and OS and PFS was examined using a marginal Cox proportional hazard model for matched pairs. The interaction between KRAS status and race was tested in the model. The association between race and response to therapy and adverse events were examined using a marginal logistic regression model. Results: In total, 392 patients were matched and included in the final data set. No difference in OS (hazard ratio [HR], 0.92; 95% confidence interval [CI], 0.73‐1.16), PFS (HR, 0.97; 95% CI, 0.78‐1.20), or response to therapy (odds ratio [OR], 1.00; 95% CI, 0.65‐1.52) was observed between Black and White patients. Patients with KRAS mutant status (HR, 1.31; 95% CI, 1.02‐1.67), a performance statusscore of 1 (reference, a performance status of 0; HR, 1.49; 95% CI, 1.18‐1.88), or ≥3 metastatic sites (reference, 1 metastatic site; HR, 1.67; 95% CI, 1.22‐2.28) experienced worse OS. Black patients experienced lower rates and risk of grade ≥3 fatigue (6.6% vs 13.3%; OR, 0.46; 95% CI, 0.24‐0.91) but were equally likely to be treated with a dose reduction (OR, 1.09; 95% CI, 0.72‐1.65). Conclusions: No difference in OS, PFS, or response to therapy was observed between Black patients and White patients in an equal treatment setting of the CALGB/SWOG 80405 randomized controlled trial. Lay Summary: Despite improvements in screening and treatment, studies have demonstrated worse outcomes in Black patients with colorectal cancer. The purpose of this study was to determine whether there was a difference in cancer‐specific outcomes among Black and White patients receiving equivalent treatment on the CALGB/SWOG 80405 randomized clinical trial. In this study, there was no difference in overall survival, progression‐free survival, or response to therapy between Black and White patients treated on a clinical trial. These findings suggest that access to care and differences in treatment may be responsible for racial disparities in colorectal cancer. Abstract : In a secondary analysis of the CALGB/SWOG 80405 randomized clinical trial, there was no difference in overall survival, progression‐free survival, or response to therapy between matched Black patients and White patients with advanced or metastatic colorectal cancer. Because racial disparities in metastatic colorectal cancer survival were not seen in an equal treatment setting, differences in access to care and treatment delivery may be responsible for the racial disparities observed in epidemiological studies.